Enhancement of Tc in BiS2-based superconductors NdO0.7F0.3BiS2 by substitution of Pb for Bi. (December 2015) - Demura, S.; Fujisawa, Y.; Otsuki, S.; Ishio, R.; Takano, Y.; Sakata, H.
Abstract: We succeed in enhancement of a superconducting transition temperature ( T c ) for NdO0.7 F0.3 BiS2 single crystal by partial substitution of Pb for Bi. The T c increases with increasing Pb concentration until 6%. The maximum T c zero is 5.6 K, which is the highest value among BiS2 -based based superconductors synthesized under an ambient pressure. Pb substitution for Bi induces lattice shrinkage along the c -axis. These results reflect that superconductivity in this system is responsive to the lattice strain. Highlights: We synthesized NdO0.7 F0.3 BiS2 single crystals by substitution of Pb for Bi. The superconducting transition temperature increases upon Pb substitution until 6%. The substitution of Pb introduces a lattice shrinkage along c -axis. This results indicate BiS2 -based superconductors are sensitive for a lattice strain.